Complications of primary and revision functional endoscopic sinus surgery for chronic rhinosinusitis. (9th October 2013) - Krings, James G.; Kallogjeri, Dorina; Wineland, Andre; Nepple, Kenneth G.; Piccirillo, Jay F.; Getz, Anne E.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The goal of this study was to determine the incidence of major complications following primary and revision functional endoscopic sinus surgery (FESS). In addition, this study aimed to determine factors associated with the occurrence of complications including patient and provider characteristics and the use of image guidance system (IGS) technology. Study Design Retrospective cohort analysis of California and Florida all‐payer databases from 2005 to 2008. Methods The rates of major surgical complications (skull base, orbital, and hemorrhagic) after primary and revision FESS were calculated, and bivariate analyses were performed to investigate relationships of complications with demographic and clinical characteristics. A multivariate model was used to determine risk factors for the occurrence of major complications. Results Among 78, 944 primary FESS cases, 288 major complications were identified representing a complication rate of 0.36% (95% CI 0.32%–0.40%). The major complication rate following revision cases (n = 19; 0.46%) and primary cases (n = 288; 0.36%) was similar (OR = 1.26; 95% CI 0.79–2.00). Multivariate analysis showed that patients who were >40 years old, had a primary payer of Medicaid, had surgery involving the frontal sinus, or had image guidance during surgery were at higher risk for major complications. Conclusion The rate of major complications (0.36%) associated with primary FESS is lower than earlier reports. The rate of major complications following revision FESS (0.46%) was found to be similar to primary cases. IGS, insurance status, age, and extent of surgery were found to be associated with an increased risk of major complications following FESS. Level of Evidence 2C. Laryngoscope, 124:838–845, 2014